Evaluation of TEM specimen quality prepared by focused ion beam using symmetry breaking index of convergent-beam electron diffraction. (15th January 2021) - Morikawa, Daisuke; Ageishi, Masaki; Sato, Kaori; Tsuda, Kenji; Terauchi, Masami
Abstract: Degradation of the crystalline quality of transmission electron microscopy specimens in silicon prepared with different conditions has been examined using convergent-beam electron diffraction (CBED). The specimens are prepared using focused ion beam (FIB) with different accelerating voltages, Ar-ion milling and crushing method. Symmetry breaking of CBED patterns was quantitatively evaluated by symmetry breaking index S, which has been previously reported. The degradation and inhomogeneity of the FIB specimen were suppressed by decreasing the accelerating voltages of the FIB fabrication in the final process.